804 Accessory Extensor Digitorum Brevis Manus Muscle Presenting as a Painful Dorsal Hand Swelling - a Case Report. (19th August 2022) - Noton, T; Magill, H; Kazzazi, F; Lumsdaine, W; Bremner-Smith, A
Abstract: Hand and wrist pain are common presenting complaints in General Practice, Emergency Departments, and plastic surgery clinics across the UK. We present the case of a 43-year-old male who initially presented to his General Practitioner with an 18-month history of progressive pain and intermittent swelling to the dorsum of his right hand and wrist. Magnetic resonance imaging (MRI) and ultrasound (US) performed privately, when his symptoms first presented, were inconclusive, demonstrating generalised tenosynovitis. The patient had previously tried local steroid injections and shockwave therapy prior to being referred, neither of which relieved his symptoms. On examination in clinic, there was subtle fusiform prominence over the radio-dorsal aspect of his right hand, with tenderness on palpation and on extension of the wrist. An up-to-date MRI scan was performed which revealed an accessory extensor digitorum brevis manus (EDBM) muscle at the dorsal aspect of the right hand and wrist. The patient opted for excision of the accessory EDBM muscle, which was performed without complication under general anaesthetic and regional block. He made an unremarkable recovery. Whilst accessory extensor muscles in the hand are not unheard-of, variant EDBM muscles only account for around 1% of these, and only a handful have been documented in literature. When patients present with a painful swelling in the dorsum of the hand or wrist, which is exacerbated with repetitive use, a diagnosis of an accessory EDBM muscle should be considered a differential.